1998
DOI: 10.2337/diab.47.1.50
|View full text |Cite
|
Sign up to set email alerts
|

GLUT2 in Pancreatic Islets: Crucial Target Molecule in Diabetes Induced With Multiple Low Doses of Streptozotocin in Mice

Abstract: In mice, diabetes can be induced by multiple low doses of streptozotocin (MLD-STZ), i.e., 40 mg/kg body wt on each of 5 consecutive days. In this model, diabetes develops only when STZ induces both beta-cell toxicity and T-cell-dependent immune reactions. The target molecule(s) of MLD-STZ-induced beta-cell toxicity are not known, however. In this study, we report that GLUT2 is a target molecule for MLD-STZ toxicity. Ex vivo, a gradual decrement of both GLUT2 protein and mRNA expression was found in pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(101 citation statements)
references
References 25 publications
(38 reference statements)
4
93
1
2
Order By: Relevance
“…STZ is recognized by glucose transporter GLUT2, and mainly targeted to pancreatic β cells 36 . The half-life of STZ is extremely short between 5–15 min in vivo and therefore cannot function for a prolonged time.…”
Section: Discussionmentioning
confidence: 99%
“…STZ is recognized by glucose transporter GLUT2, and mainly targeted to pancreatic β cells 36 . The half-life of STZ is extremely short between 5–15 min in vivo and therefore cannot function for a prolonged time.…”
Section: Discussionmentioning
confidence: 99%
“…The glucose analogue STZ is reported to be transported into β-cells by the glucose transporter 2 (GLUT2) for exerting its apoptotic effect (Wang and Gleichmann 1998). While we did not study the effect of genistein on GLUT2 protein expression in mouse islets, our recent studies found that genistein had no such an effect in cultured β-cells (Fu and Liu 2009), suggesting that improvement of islet β-cell mass and survival by genistein may not be due to modulation of GLUT2 expression, thereby preventing STZ influx in β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…A PPARα-agonist also induced GLUT2 expression in islets but the effect on glucokinase was not documented [109]. Improved glucose metabolism, however, has not been a consistent outcome of PPARγ induction [103].…”
Section: Peroxisome Proliferator-activated Receptors and β-Cell Functionmentioning
confidence: 99%